Evaluación de la inclusión de estudiantes con discapacidad visual en instituciones educativas de la ciudad de Quito - Caviedes Rodríguez, Cristina Alejandra (2015)
To offer the opportunity of which the children with visual disability receive a pedagogic attention in the educational regular institutions allows them to educate in equality of conditions that the rest of children of the same age, being useful the time and the resources that the teacher uses, which redounds to the improvement of the educational quality in general. The present investigation had as general aim, evaluate the process of incorporation of the students with visual disability to the educational regular system, in several institutions of the city of Quito. I think that this topic performs supreme importance, since it is necessary to know the problems that they present in the educational institutions on having received these students, having known if the teachers are prepared to assume this challenge and if they realize the relevant curricular adaptations, in agreement to the individual differences of every student. The investigation was effected in the following educational inclusive institutions, which receive the students who go away of the Institute of Special Education "Mariana de Jesus": Educational Unit Milenio Bicentenario, Educational Municipal Unit Julio E. Moreno, Sagrados Corazones de Rumipamba, Mercedes de Jesus Molina (Conocoto), Claudio Monteverdi and it allowed to have a clear and concise vision of how one is giving this process, for which was realized you interview executives and surveys were applied to the teachers. Since result of this investigation will be able to have a statistical base and a veracious knowledge of how this process has influenced the life of the student in general, and that the included students have achieved benefits; simultaneously to know if the educational institutions have changed his philosophy, culture, pedagogic practices, with regard to the students who present disability.